2023
DOI: 10.1038/s41598-023-30890-8
|View full text |Cite
|
Sign up to set email alerts
|

The lack of keratinized mucosa as a risk factor for peri-implantitis: a systematic review and meta-analysis

Abstract: This study aimed to investigate the effect of the lack of keratinized mucosa on the risk of peri-implantitis, while also accounting for possible confounding factors. A literature search was conducted in PubMed and Scopus, including human studies that assessed the presence and width of keratinized mucosa in relation to the occurrence of peri-implantitis. Twenty-two articles were included, and 16 cross-sectional studies we meta-analyzed. The prevalence of peri-implantitis was 6.68–62.3% on patient-level and 4.5–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…This fact agrees with the results of Ravidà et al (2022) [ 33 ], who showed that KMW < 2 mm might be a risk factor for developing peri-implant diseases, even though this fact is dependent on other site-specific characteristics, such as mucosa thickness, supracrestal tissue height, peri-implant bone thickness, pocket depth and superstructure crown design. The results of this study are consistent with previous research that has shown the importance of keratinized mucosa in maintaining implant stability and preventing mucositis [ 34 , 35 ]. The findings also suggest that castable UCLA abutments may be advantageous in reducing the risk of abutment fracture compared to machined solid abutments.…”
Section: Discussionsupporting
confidence: 92%
“…This fact agrees with the results of Ravidà et al (2022) [ 33 ], who showed that KMW < 2 mm might be a risk factor for developing peri-implant diseases, even though this fact is dependent on other site-specific characteristics, such as mucosa thickness, supracrestal tissue height, peri-implant bone thickness, pocket depth and superstructure crown design. The results of this study are consistent with previous research that has shown the importance of keratinized mucosa in maintaining implant stability and preventing mucositis [ 34 , 35 ]. The findings also suggest that castable UCLA abutments may be advantageous in reducing the risk of abutment fracture compared to machined solid abutments.…”
Section: Discussionsupporting
confidence: 92%
“…This narrative review revealed that three of nine studies [ 7 , 9 , 13 ] identified the lack of keratinized mucosa as a risk factor for developing peri-implantitis. Brito et al [ 10 ] concluded that the presence of an appropriate zone of keratinized tissue results in better peri-implant tissue health, which is consistent with the research of Thoma et al [ 5 ] and Stefanini et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the 2017 World Workshop could not establish the necessity of KT for maintaining peri‐implant health (Araujo & Lindhe, 2018; Heitz‐Mayfield & Salvi, 2018; Schwarz et al, 2018), more recent systematic reviews indicated that a reduced width of KT is associated with soft‐tissue inflammation, increased biofilm accumulation, marginal bone loss and increased prevalence of peri‐implantitis (although with some heterogeneity among the studies) (Heydari et al, 2021; Longoni et al, 2019; Mahardawi et al, 2023; Ramanauskaite et al, 2022; Ravida et al, 2022). Soft‐tissue augmentation at implant sites has gained prominence for preventing these biological complications.…”
Section: Introductionmentioning
confidence: 99%